KEHIDUPAN SUFISTIK PADA PONDOK PESANTREN BIBAH{RI âASFARAâ SANANREJO, TUREN, MALANG - Musthofa, Musthofa (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2014)
Abstract: The study is about Sufiâs life in Bibahri Asfarah Islamic boarding school, Sananrejo, Turen, Malang. This study was conducted to understand how the sufiâs life in associated with the life prior boarding school stay, how the method to the sufiâs life, hal (circumstance of mind when practicing) and gayah (ending circumstance of lives after practice) is. This study employs a phenomenological approach. The methods of data collection are documentation, interviews, observation, and triangulation. Data analysis methods use several steps such as data reduction, data display and conclusion (verification). The students of the boarding school consist of students with diverse life backgrounds. Which are mapped into three categories namely al-Fussaq, Al-Fusyl, and Al-Abriya. The first category, Al-Fussaq, consists of ex-drug addict, alcohol drunk, and those who are disobedient to parents. The second category, Al-Fusyl, consists of those who are failed in either family or economy. While the third category, Al-Abriya, consists of former employees or alumni from the other boarding schools. The method to the sufiâs life with the practices performed which are mapped into two kinds namely inward and outward practices. The inward practices include salawat (prayer for the prophet), istigosah (mass prayer), Asmaul Husna (reciting names of God), Yaseen recital. The outward practices include traveling, cleaning the Islamic boarding school environment, installing paving and ornaments, making bricks, taking care of animal, becoming a secretary and treasurer of the boarding school. Those practices are called riadah. The soul circumstances (ahwal) while performing those practices could be described that they feel muhasabah (introspective), wusul (pure), happy, excited, hauf (fearful) and rajaâ (hopeful). Meanwhile, after performing those practices the students experience new life changes that they feel happy, joyful, faithful, true, peaceful, pure, convinced, modest, ascetic, and sincere.